Seroprevalence and risk factors for toxoplasmosis in large ruminants in northern Punjab, Pakistan - Nisar Ahmad; Mazhar Qayyum (Journal of Infection in Developing Countries)
Introduction: Toxoplasmosis is a widespread zoonosis that causes significant economic losses due to abortions and other developmental disabilities in livestock animals. The objectives of the current study were to determine the prevalence and associated risk factors of Toxoplasma gondii infection in cattle and buffaloes in northern parts of Punjab, Pakistan, where no such work previously existed. Methodology:Serum samples obtained from 400 cattle and 422 buffaloes present on different private and government-owned farms were tested for anti-Toxoplasma IgG and anti-Toxoplasma IgM antibodies by using enzyme linked immunosorbent assay (ELISA). Additional data, including water sources, hygienic status at the farm, management practices, size of the herd, and presence of cats in the vicinity of the farm were obtained using a questionnaire in surveys and interviews. Results: The overall prevalence of infection was 19.75% (79/400) in cattle and 15.16% (64/422) in buffaloes. IgG antibodies were found in 75 (18.75%) cattle and 58 (13.74%) buffaloes, while IgM antibodies were found in 9 (2.25%) cattle and 10 (2.37%) buffaloes. Seroprevalence was significantly higher in females and older animals of both species. Seroprevalence was found to be associated with poor hygienic conditions, extensive management practices, and presence of cats in the surrounding areas. No difference of seroprevalence was observed with respect to different breeds, location, water source, and herd size. Conclusion: The present study found that T. gondii is prevalent in large ruminants in northern Punjab, and may have important implications for the livestock industry and public health.